Iron status and dietary iron intake of female blood donors. Issue 3 (22nd July 2013) - Booth, Alison O.; Lim, Karen; Capper, Hugh; Irving, David; Fisher, Jenny; McNaughton, Sarah A.; Riddell, Lynn; Keller, Anthony; Nowson, Caryl A.
Abstract : Background: The aim was to assess iron status and dietary iron intake in a sample of premenopausal female regular and new blood donors. Study Design and Methods: Premenopausal women blood donors were invited to participate. Blood samples were analyzed for serum ferritin and hemoglobin. An iron checklist assessed dietary iron intake. Donors were classified as regular donors or new donors. Results: Twenty‐one new donors (mean [SD] age, 28.6 [6.0] years; body mass index [BMI], 25.6 [4.5] kg/m 2 ) and 172 regular donors (mean age, 29.4 [5.5] years; BMI, 24.7 [3.8] kg/m 2 ) participated. Fifty percent of regular donors and 24% of new donors had depleted iron stores (serum ferritin <15 μg/L; difference p = 0.036). Dietary iron intake was higher in regular donors (mean [SE], 12.6 [0.7] mg/day) compared to new donors (9.9 [0.4] mg/day; p = 0.006). Eighty‐five percent of regular donors and 79% of new donors met the estimated average requirement for iron. Conclusions: Despite the fact that most of these donors had an adequate dietary iron intake, more than half of the blood donors had depleted iron stores. Increasing dietary iron intake through supplements and/or dietary means is expected to be necessary to maintain adequate iron status in this group.